2013
DOI: 10.1039/c3cp52885e
|View full text |Cite
|
Sign up to set email alerts
|

Redox activity distinguishes solid-state electron transport from solution-based electron transfer in a natural and artificial protein: cytochrome C and hemin-doped human serum albumin

Abstract: Integrating proteins in molecular electronic devices requires control over their solid-state electronic transport behavior. Unlike "traditional" electron transfer (ET) measurements of proteins that involve liquid environments and a redox cycle, no redox cofactor is needed for solid-state electron transport (ETp) across the protein. Here we show the fundamental difference between these two approaches by macroscopic area measurements, which allow measuring ETp temperature dependence down to cryogenic temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 45 publications
(53 reference statements)
5
68
1
Order By: Relevance
“…This lack of correlation between ETp and protein monolayer width (electrode separation) underscores that different orientations of the same protein can present distinct charge transport media between the two electrodes. This can also be related to the cofactor position with respect to the electrodes because, as we have shown previously, cofactors are crucial mediators in ETp, even though, in contrast to ET, they do not need to be redox-active to achieve efficient ETp (28,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lack of correlation between ETp and protein monolayer width (electrode separation) underscores that different orientations of the same protein can present distinct charge transport media between the two electrodes. This can also be related to the cofactor position with respect to the electrodes because, as we have shown previously, cofactors are crucial mediators in ETp, even though, in contrast to ET, they do not need to be redox-active to achieve efficient ETp (28,33).…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to note that the barrier for ETp across WT CytC is influenced and possibly dominated by the protein's contact to the electrode, and as such it is distinct from the E a of ET reactions between a donor and acceptor (usually determined by the driving force and reorganization energy), as treated by Marcus theory. In this context, it is important to note that we have previously shown that in contrast to an electrochemical process, ETp across a protein does not require a redox process (33).…”
Section: Discussionmentioning
confidence: 99%
“…Eq. 10 can be used directly in the modeling of electron transport through solid-state protein junctions (27,28) or redox junctions (29)(30)(31)(32). The semiconductor's band structure should be used for quantitative descriptions of conduction through typical FET bridges.…”
Section: Significancementioning
confidence: 99%
“…Finally, it should be noted that solid-state electron transport studies using mutant forms of cytochrome c integrated into a molecular electronic device (contacted to two electrodes) have produced useful insights on the importance of the protein’s electronic coupling to the electrode surface and orientation on the current that flows through the device [75,77,78]. Fundamentally, the current flow through the solid-state device is an electron flux across the protein without the need for a redox process, while the current measured in the electrochemical process is due to electronsshuttling to and from the Fe(III) and Fe(II) oxidation states of the heme.…”
Section: Discussionmentioning
confidence: 99%